Legal Development of the Validity of Electronic Mortgage Certificates in the Land Registration System in Indonesia - Harjono, Dhaniswara K (Faculty of Law, Universitas Sebelas Maret, 2022)
Electronic encumbrance Right is one of the breakthroughs made by the Minister of Agrarian Affairs to improve services in the land sector and support the Government in realizing a digital bureaucracy in Indonesia. This paper aims to deeply examine the validity and execution of such electronic Encumbrance Right Certificates.The main findings show that the electronic Encumbrance Right Certificate cannot be separated from the provisions of the Electronic Information and Transactions law, which lays out the conditions that must be met for the validity of electronic certificates and their status as evidence in court. The problem of authentication differs from the acknowledgement of electronic data. If the data or electronic documents are accepted or legally recognized, the authentication process for the data will automatically follow. The authentication process is a matter of technology while acknowledging electronic documents involves formal recognition in laws and regulations. Electronic evidence consisting of Electronic Information or Electronic Documents or the printouts produced by the Electronic System is legal evidence. On the other hand, if the Electronic Information is not generated through the Electronic System, the evidence cannot automatically be assessed as valid. Such electronic information can be used as electronic evidence if the authenticity, accuracy, and integrity have been verified through an information technology forensic audit